The Certainty of Uncertainty. A Discussion of Patrik Aspers’ Book - Bruce G. Carruthers (Sociologica)
Patrik Aspers’ recent book on uncertainty offers a welcome opportunity to explore how risk and uncertainty are socially structured. I summarize and discuss Aspers’ contribution.